Fusion of Chitin-Binding Domain From Chitinolyticbacter meiyuanensis SYBC-H1 to the Leaf-Branch Compost Cutinase for Enhanced PET Hydrolysis - Xue, Rui; Chen, Yinping; Rong, Huan; Wei, Ren; Cui, Zhongli; Zhou, Jie; Dong, Weiliang; Jiang, Min (Frontiers in Bioengineering and Biotechnology, 2021)
Polyethylene terephthalate (PET) is a mass-produced petroleum-based non-biodegradable plastic that contributes to the global plastic pollution. Recently, biocatalytic degradation has emerged as a viable recycling approach for PET waste, especially with thermophilic polyester hydrolases such as a cutinase (LCC) isolated from a leaf-branch compost metagenome and its variants. To improve the enzymatic PET hydrolysis performance, we fused a chitin-binding domain (ChBD) from Chitinolyticbacter meiyuanensis SYBC-H1 to the C-terminus of the previously reported LCCICCG variant, demonstrating higher adsorption to PET substrates and, as a result, improved degradation performance by up to 19.6% compared to with its precursor enzyme without the binding module. For compare hydrolysis with different binding module, the catalytic activity of LCCICCG-ChBD, LCCICCG-CBM, LCCICCG-PBM and LCCICCG-HFB4 were further investigated with PET substrates of various crystallinity and it showed measurable activity on high crystalline PET with 40% crystallinity. These results indicated that fusing a polymer-binding module to LCCICCG is a promising method stimulating the enzymatic hydrolysis of PET.